2007
DOI: 10.1002/uog.4078
|View full text |Cite
|
Sign up to set email alerts
|

A diffusion‐weighted template for gestational age‐related apparent diffusion coefficient values in the developing fetal brain

Abstract: Objective To determine the pattern of apparent diffusion coefficient (ADC) values in the normal fetal brain obtained with diffusion-weighted images (DWI) on magnetic resonance imaging (MRI) as a template for normal brain development throughout gestation. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 24 publications
8
45
0
Order By: Relevance
“…4,5 Our observation of a decline in ADC values in the thalamus, pons, and cerebellum with increasing gestational age is similar to the largest study of fetal DWI in 78 sedated fetuses by Schneider et al 4 However, it is interesting to note that they observed an increase in ADC values in the periatrial and frontal WM and basal ganglia from 23 to 29 weeks’ gestation, with a decrease in ADC values from 30 to 36 weeks’ gestation. These differences in observation could be the result of the size and shape of ROIs because our ROIs were adjusted depending on the size of the fetal brain.…”
Section: Discussionsupporting
confidence: 86%
“…4,5 Our observation of a decline in ADC values in the thalamus, pons, and cerebellum with increasing gestational age is similar to the largest study of fetal DWI in 78 sedated fetuses by Schneider et al 4 However, it is interesting to note that they observed an increase in ADC values in the periatrial and frontal WM and basal ganglia from 23 to 29 weeks’ gestation, with a decrease in ADC values from 30 to 36 weeks’ gestation. These differences in observation could be the result of the size and shape of ROIs because our ROIs were adjusted depending on the size of the fetal brain.…”
Section: Discussionsupporting
confidence: 86%
“…It provides a measure of tissue complexity and rises during late fetal life with a steady decline during infancy [17-22]. A high ADC value is seen in chronic damaged white matter; however, a low ADC value indicates acute ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…3). Studies have also shown that there is a decline in mean diffusivity values of the white matter during gestation, 26,29,30 which is less marked than that observed in the deep gray nuclei 28,30 (Fig. 3).…”
Section: Glennmentioning
confidence: 87%